Howling On the Road: Visions of the Beat Generation Today - Périz Rodríguez, Carmen (Journal of Artistic Creation and Literary Research, 2025)
The Beat Generation has had a great impact upon audiences, readers and critics. However, at the time of its birth, its members gained little recognition. The themes presented in their works -sex, drugs, jazz, and social non-conformity- were considered frivolous and lacking in literary quality by many critics. The purpose of this paper is to explore the influence of the Beat Generation on today’s cultural sphere. The paper explores two main texts, On the Road by Jack Kerouac and Howl by Allen Ginsberg. The Beat Generation continues to inspire contemporary society in a wide range of cultural fields.